Insights into systemic resilience from innovation research; Systemische Resilienz - Einsichten aus der Innovationsforschung - Florian Roth; Philine Warnke; Pia Niessen; Jakob Edler (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2021)
In the wake of the COVID-19 pandemic, the concept of resilience has become an increasingly important guiding principle. Voices from politics, business and society are calling for strategies which help to better weather crises or ideally prevent them from occurring in the first place.
urn:nbn:de:0011-n-6486362
Keywords: 330